Volatilidade de renda e a cobertura do Programa Bolsa Família - Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This text argues that the criteria used to define Bolsa Família benefits and the criteria used to establish coverage targets are inconsistent. While individual concession criteria are that beneficiaries should be paid for two years if they do not suffer large upward income mobility, the coverage targets are estimated using a household surveys that interview a cross-section of individuals and thus do not follow them through time. If poor individuals suffer income volatility the two criteria are inconsistent and Bolsa Família will always have an eligible public that outnumbers its coverage targets. The monthly employment survey (PME) follows a four month panel of individuals and its thus used to estimate the income volatility of those whose profile is close to the Bolsa Familia profile. My conclusions are that income volatility is high and that four month longitudinal poverty is about 2/3 higher than one month crosssection poverty. The conclusion is that the methodology used to estimate Bolsa Família coverage targets should be changed.
Keywords: I38; 330